Economic Growth in Ghana : Determinants and Prospect - Raggl, Anna K. (World Bank, Washington, DC, 2014)
This paper employs a simple cross-country panel framework to assess the determinants of growth in Ghana's gross domestic product over the past four decades. A set of standard covariates is used to explain growth rates. Natural resource variables are included because the effects of natural resource rents in gross domestic products are of particular interest for Ghana. Using the preferred specification, Ghana's growth potential is predicted for the upcoming decades under different scenarios. The results indicate that under the most pessimistic scenario of no improvements in the determinants of growth compared with the period 2005-09, Ghana's gross domestic product per capita growth rates will stagnate at approximately 4.5 percent during the next decade and decrease thereafter. If the policy measures and country characteristics improve in the way they did in the past three decades, average per capita growth rates of roughly 5.5 percent could be reached during 2015-34. Taking into account the expected oil production until 2034 adds 0.6 percentage points to projected gross domestic product growth rates on average.